News Notes. - Griffin, Charles H. (The Accounting Review, 1968)
Abstract The article presents news items related to colleges and universities, published in July 1968 issue of "The Accounting Review." Richard D. Bradish will join the faculty of the School of Business Administration, Sacramento State College, Sacramento, California, in June, 1968 as Professor and Chairman of the Department of Accounting and Quantitative Methods. In the University of Southern California, A. N. Mosich has been promoted to professor. In the University of Florida, Carl A. Anderson has been appointed Assistant to the Dean of the College of Business Administration. Keith Baker accepted a position as Assistant Professor of Accounting at the University of Michigan, beginning in January 1968. Drake University. Merrill B. Dilley, of Drake University will be on leave for a year beginning June 1,1968. Wichita State University. Eldon Lewis was appointed Chairman of the Accounting Department of Wichita State University in June, 1967. John P. Deehan, Seton Hall University, has been appointed to the New Jersey Interracial Council, an advisory group of business and professional leaders.